Первоначальное направление полета в экспериментах по "хомингу" - Смогоржевский, Л.А. (Вестник зоологии, 1967)
The author considers the question on the meaning of the flight initial (starting) direction of birds' transmigration in homing experiments. The initial direction, which Matthews called "senseless", is of great biological importance, as it helps birds to restore a migratory direction and later on more or less easily to make corresponding corrections of the direction towards "home". Such an initial orientation in homing is called "pseudo-migratory" instead of "senseles"» and the direction is called "migratory"